Combined neutron and laser techniques for technological and compositional investigations of hollow bronze figurines. Issue 3 (21st January 2015) - Agresti, Juri; Osticioli, Iacopo; Guidotti, Maria Cristina; Capriotti, Giuseppina; Kardjilov, Nikolay; Scherillo, Antonella; Siano, Salvatore
Abstract : Neutron tomography (NT), time of flight neutron diffraction (TOF-ND) and laser induced plasma spectroscopy (LIPS) were combined in the archaeometallurgical study of hollow bronze figurines. Abstract : Here, an innovative non-invasive multi-analytical approach for the archaeometallurgical characterisation of ancient bronze artefacts using high resolution neutron tomography, time of flight neutron diffraction, and laser induced plasma spectroscopy has been investigated. We show its effectiveness through an example application aimed at describing the crafting processes, characterising the alloy compositions and deterioration phenomenologies of three small bronze figurines from the antiquarian collection of the Egyptian Museum of Florence. The present methodology has allowed unprecedented overall archaeometallurgical descriptions of these artefacts based on the detection of fine morphological details, degree of mineralisation, elemental and phase composition of the metal walls, and mineral contents of the core materials. Such an approach can be extended to other hollow copper alloy artefacts in order to identify their raw materials and interpret their technological processes.